Nonlinear pricing under regulation: Comparing cap rules and taxes in the laboratory - José G. Nu\~no Ledesma; Steven Y. Wu (Banco de México, 2022)
We report an experiment contrasting the impacts of a tax and a cap rule in a single-product market with two privately-informed buyers. We discuss the effects on choice set and consumer surplus. The policy environment varies across treatments. With regulations, we aim to halve the size of the unregulated large option. Compared to the regulation-free baseline, sellers facing a cap attempt to serve the buyers separately with similar frequency. With a tax, subjects are less likely to offer menus with two alternatives. We find that consumer surplus remains unaffected under a cap rule, while buyers with high appreciation for the product see their surplus diminished by the tax. These results have implications for policy making in the food retail industry and others where authorities aim to regulate consumption while protecting consumer surplus.
Keywords: C9; D82; L51; 330; Experiment; Nonlinear pricing; portion cap rule; quantity restriction; tax